Language contacts at the crossroads of disciplines - Paulasto, Heli; Merilainen, Lea; Riionheimo, Helka; Kok, Maria (Cambridge Scholars Publishing, 2014)
This volume offers a cross-disciplinary insight into language contact research, bringing together fresh empirical and theoretical studies from various fields concerning different dimensions of language contact and variation, second language acquisition and translation. In the present-day world of globalization, population mobility and information technology, the themes of multilingualism and contact-induced language change are as topical as ever, and research on language contacts and cross-linguistic influence has expanded rapidly during the last few decades. Along with the increasing specialization of related disciplines, their research perspectives, methods and terminology have become dispersed, although language contact phenomena themselves can rarely be confined within the scope of a single discipline. This collection of articles creates dialogue between researchers from different scientific backgrounds and thus widens readers' perspectives on language contact phenomena. When language contact is re-defined to include the mental or cognitive level of contact between different languages and varieties in the minds of language learners or translators, salient links are created between the different disciplines dealing with this subject matter.--Back Cover.